Innate immunity mediated by MyD88 signal is not essential for induction of LPS-specific B cell responses but is indispensable for protection against Salmonella enterica serovar Typhymurium infection() - Ko, Hyun-Jeong (2009)
Salmonella organisms are gram-negative and facultative anaerobic bacteria that cause typhoid fever in humans. In this study, we evaluated LPS-specific adaptive immunity in innate immune-deficient mice after oral administration of attenuated S. enterica serovar Typhymurium (S. Typhimurium) strains. Of interest, identical levels of LPS-specific IgG and IgA antibodies were elicited in the systemic (i.e., serum and spleen) and mucosal (i.e., fecal extract and small intestine) compartments of wild-type, TLR4(−/−), and MyD88(−/−) mice following oral vaccination with recombinant attenuated S. Typhimurium (RASV). Depletion of CD4(+) T cells during RASV vaccination completely abrogated the generation of LPS-specific antibodies in MyD88(−/−) mice. In addition, mRNA expression levels of a B-cell activating factor of the TNF family (BAFF) were significantly increased in the spleens of MyD88(−/−) mice after oral administration, implying that T cell–independent B cell switching might be also enhanced in the MyD88 signal-deficient condition. Of most interest, orally vaccinated MyD88(−/−) mice that possessed high levels of LPS-specific IgG and IgA, which had neutralizing effect against Salmonella, died earlier than non-vaccinated wild-type mice following lethal oral challenge with virulent Salmonella species. These results suggest that innate immunity mediated by MyD88 signal is dispensable for induction of LPS-specific antibody responses following oral administration of attenuated Salmonella strains but indispensable for efficient protection.